Hierarchical responsive micelle facilitates intratumoral penetration by acid-activated positive charge surface and size contraction. (April 2021) - Ma, Mengcheng; Chen, Yafang; Zhao, Mingda; Sui, Junhui; Guo, Zhihao; Yang, Yuedi; Xu, Zhiyi; Sun, Yong; Fan, Yujiang; Zhang, Xingdong
Abstract: Integrating these features of acid-activated positively charged surface and size contraction into single nanoparticle would be an effective strategy for enhancing cellular uptake, intratumoral penetration and accumulation. Here, hierarchical responsive micelle (HVDMs) was developed via RAFT reaction as multifunctional polymer-drug conjugate for maximizing penetration and therapeutic effect against MCF-7 tumor by combining positively charged surface with size contraction: surface zeta-potential reversal (−2 to +12 mV) by protonation of PHEME and size contraction ( 81– 41 nm) by simultaneous hydrophobic/hydrophilic conversion (pH ≈ 6.7); the disintegration of hydrazone bond between hydrophobic PVB and DOX triggered drug release (pH ≈ 5.0). The in vitro structural stabilization, cellular uptake and anti-proliferative efficiency were significantly higher than other control groups (CVDMs and HSDMs) at pH 6.7. The markedly increased penetration depth, cellular internalization and anti-tumor efficiency were confirmed in 3D MCSs spheroids at pH 6.7, and the ex vivo DOX fluorescence images further verified obvious penetration and accumulation in internal region of solid tumor. The antitumor effect in vivo demonstrated that HVDMs accelerated tumor atrophy, induced intratumoral cells apoptosis and alleviated system toxicity. Graphical abstract: Image 1